Labor demand response to labor supply incentives: Lessons from the German Mini-Job Reform - Gabriela Galassi (Bank of Canada, 2021)
This paper analyzes how firms respond to changes in tax benefits for low-earning workers and how, through equilibrium effects, such policies also affect non-targeted, high-earning workers. I explore establishment-level outcomes around Germany's 2003 Mini-Job Reform, which entailed a significant expansion of tax benefits for low-earning workers. Firms' responses are decomposed in terms of the scale effects that arise from lower labor costs and the substitution effects that are due to changes in the relative prices of low- and high-earning employment post-reform. Using a differences-in-differences approach, I document that highly exposed establishments-those with a high proportion of low-earning workers pre-reform-expand their number of employees relative to non-exposed establishments-those with a low proportion of such workers. Importantly, this relative expansion is tilted towards high-earning workers, a group that is not the target of the tax benefits. In addition, non-exposed establishments substitute employment towards low-earning workers without expanding at the same pace. My findings are consistent with a model of the labor market that features tax sharing between workers and firms and simultaneous shifts in labor supply and demand after changes in tax benefits for low-earning workers. In this setting I illustrate that the employment growth the policy intended is accompanied by a reallocation of employment and production between highly exposed firms and non-exposed firms, and this may result in an efficiency loss.
Keywords: H20; H24; H32; E24; E64; I38; J23; J38; 330; Labour markets; Firm dynamics; Economic models